P881 Is occupation a risk factor for developing Inflammatory Bowel Disease? A case-control study. (30th January 2023) - Mauriz Barreiro, M V; Ruano-Ravina, A; Ferreiro-Iglesias, R; Baston-Rey, I; Porto-Silva, S; Nieto-Garcia, L; Martinez-Seara, X; Martin-Gisbert, L; Dominguez-Munoz, J E; Barreiro-de Acosta, M
Abstract: Background: The role of occupation is well established for different diseases. Nevertheless, there is a lack of information on the role of occupation on the onset of inflammatory bowel diseases. Many occupations entail the exposure of different toxic substances that may reach the bowel through different biological pathways (bloodstream or digestive tract) and act as possible triggers of such diseases, mainly Crohn′s disease and ulcerative colitis. The aim of this study is to identify if there is a role of occupation on the onset of IBD using a case-control study. Methods: A prospective case-control, single-center study was designed. All Incident cases with any of the main IBD diseases (ulcerative colitis, Crohn's disease and unclassified colitis) were consecutively included. Controls were patients selected from the consults and endoscopic room of the Digestive Unit of Clinical Hospital of Santiago de Compostela without any autoimmune chronic disease. Cases are patients with IBD disease diagnosed 3 or less months prior to the inclusion and over 18 years old. Cases and controls were recruited simultaneously and controls followed a sex and age frequency matching with cases. All participants were recruited from June 2020 to September 2022. A detailed questionnaire describing the occupations held and time of them was used. Blue-collar jobs have been defined as those entailing the highest risk occupational exposures and are also mentioned as manual workers. White-collar jobs are usually those with more office-related work, but also with teaching or health sector. To analyze the results, we used a logistic regression. A subgroup analysis was performed by each of the three diseases considered. Results: 129 patients with incident IBD (73 with ulcerative colitis, 51 with Crohn's disease and 5 with indeterminate colitis) and 114 controls were included. Comparing patients with IBD with controls, there were no statistically significant differences between type of work, working hours, contact with animals or physical activity at work. Among the patients with IBD, there were no differences in the number of flares between groups (blue collar workers vs. white collar (p>0.05), outside workers vs. indoor ones (p>0.05), sedentariness vs. moderate activity or high activity (p>0.05) or animal contact vs. no contact (p>0.05)). Taking into account only patients with current work activity, the results did not change. After stratifying results according to type of IBD, there were no statistically significant differences either (table 1). Conclusion: In this study, differences between type of work, working hours, contact with animals or sedentariness were not associated with the risk of IBD nor with the activity of this disease.